Microwave ablation determines similar survival outcomes as compared to radiofrequency ablation for the treatment of hepatocellular carcinoma. (3rd July 2021) - Khan, Amer; Mostowy, Marcin; Owusu, Michael; Mutambanengwe, Mercy; Habimana, Samson; Bence, Somoskoi; Facciorusso, Antonio
ABSTRACT: Objectives: It is still unclear whether microwave ablation (MWA) outperforms radiofrequency ablation (RFA) in the treatment of hepatocellular carcinoma (HCC). Aim of this manuscript is to compare the two treatments through a meta-analysis of randomized-controlled trials (rcts). Methods: Computerized bibliographic search was performed on main databases through August 2020. The primary outcome was the complete response rate, with survival rate, disease-free survival rate, and adverse event rate as secondary outcomes. Results were expressed in terms of risk ratio (RR) and 95% confidence interval (CI) Results: Seven rcts enrolling 1143 patients were included. Rates of complete response were similar (RR 1.01, 95% CI 0.99–1.02); likewise, survival rates were constantly similar, with rrs ranging from 1.05 (0.96–1.15) at 1-year to 0.91 (0.81–1.03) at 5-year. Disease-free survival at 1-, 2-, and 3-year was similar between the two groups with RR 1.00 (0.96–1.04), 0.94 (0.84–1.06), and 1.06 (0.93–1.21), respectively. On the other hand, RR for disease-free survival at 5-year was significantly in favor of MWA (3.66, 1.32–42.27). Adverse event rate was similar between the two treatments (RR 1.06, 0.48–2.34), with bleeding and hematoma as most frequent complications. Conclusions: MWA seems to determine similar outcomes as compared to RFA.